Do private placement of equity turn around the Malaysia firm? / Nur Farhah Alya Ja'far - Ja'far, Nur Farhah Alya (Faculty of Business Management, 2017)
The population of Muslim in Malaysia stated by the Department of Statistics for 2010 is 61.3%. The contribution income for Takaful stated by Bank Negara Malaysia (BNM) is 6% in 2015 while income for insurance stated by BNM is 8.4% in 2015. Then, the influence of the Takaful is lack compared to conventional insurance in Malaysia. Besides that, based on previous research is more focus on large group numbers such whole Malaysia as a case study. Therefore, aim of the research is to identify the main factors that influence Muslim of the generation Y’s intention to participate in a self-protection scheme Takaful in Johor Bahru. Furthermore, the average of age for generation Y is 22 until 36 years old. The dependent variable is intention to participate in a self-protection scheme Takaful. The independent variable is level of awareness, social influence, service quality and promotion. This research is of the target respondents is Muslim of the generation Y’s in Johor Bahru. However, the sample technique is based on the probability of simple random. The sample size would be 110 respondents. The data collection is using a questionnaire. The method of data is used Statistical Package for Social Science (SPSS). The result from SPSS is frequency analysis, reliability test, descriptive analysis, correlation analysis and multiple regression analysis. As a result, this research to identify the main factors that influence Muslim of the generation Y’s intention to participate in a self-protection schemeTakaful in Johor Bahru. This research also will help other parties in the improvement and development of Takaful product.